Effects of the 11+ and Harmoknee Warm-up Programs on Physical Performance Measures in Professional Soccer Players - Daneshjoo, A.; Mokhtar, A.H.; Rahnama, N.; Yusof, A. (University of Uludag, 2013)
The purpose of this study was to examine the effects of the 11+ and HarmoKnee warm-up programs on performance measures in professional soccer players. Thirty-six male professional soccer players (age: 18.9 ± 1.4 years) were divided into 3 groups, the 11+, HarmoKnee and control group (n = 12 per group). The experimental groups performed the programs 3 times per week for 2 months (24 sessions), whereas the control group only performed their regular soccer training. The performance tests carried out were: 10m speed tests with and without a ball, 20m single sprint, vertical jump, Wall-Volley and Illinois agility tests. The 11+ group demonstrated significant increases from pre-to-post time points in the vertical jump (3.7%), Wall- Volley (5.4%) and Illinois agility tests (1.7%), while the HarmoKnee group showed a significant increase in Wall-Volley test, with a 5.2% increase. The repeated measures analysis revealed differences between the groups (large effect size) in the 11+ and HarmoKnee groups, compared to the control group, in 10m speed tests with and without a ball, 20m single sprint and Illinois agility tests (p < 0.05). Thus 8-weeks performing the 11+ warm-up program can enhance jump height, agility and soccer skill while the HarmoKnee program generally only improves soccer skill in young professional male soccer players. Key PointsThe 11+ improves performance by means of Illinois agility, vertical jump and Wall-Volley tests whereas HarmoKnee improves Wall-Volley test. Incorporating 11+ as a part of the warm-up program by the young teams would be beneficial in agility, leg power and soccer skill respectively.Further modification of both programs may be required to fully realize the players' speed performance potential.Data from this research can be helpful for soccer trainers in choosing programs to enhance performances in young male professional soccer players.